Molecular Biomarkers of the Mitochondrial Quality Control Are Differently Affected by Hypoxia-Reoxygenation Stress in Marine Bivalves Crassostrea gigas and Mytilus edulis - Steffen, Jennifer B. M.; Falfushynska, Halina I.; Piontkivska, Helen; Sokolova, Inna M. (Frontiers in Marine Science, 2020)
Coastal environments commonly experience oxygen fluctuations. Resulting hypoxia/reoxygenation stress can negatively affect mitochondrial functions, since oxygen deficiency impairs ATP generation, whereas a surge of oxygen causes oxidative stress. Marine intertidal bivalves are adapted to fluctuating oxygen conditions, yet the underlying molecular mechanisms that sustain mitochondrial integrity during oxygen fluctuations are not well understood. We used mRNA expression analysis to determine the potential involvement of the mitochondrial quality control mechanisms in responses to short-term hypoxia (24 h at <0.01% O2) and reoxygenation (1.5 h at 21% O2) in two hypoxia-tolerant marine bivalves, Crassostrea gigas and Mytilus edulis. We hypothesised that the genes involved in the mitochondrial quality control will be upregulated during hypoxia, and the less hypoxia-tolerant of the two studied species (M. edulis) will show a stronger dependence on transcriptional upregulation of these pathways than C. gigas. To test these hypotheses, mRNA expression of 17 (C. gigas) and 11 (M. edulis) marker genes involved in mitochondrial fusion, fission, proteolysis and mitophagy was analysed in the digestive gland of M. edulis and C. gigas in normoxia and during hypoxia-reoxygenation (H/R) stress. In the mussels, the mRNA expression of the transcripts related to mitochondrial dynamics and quality control was strongly altered during H/R stress showing a shift of the mitochondrial dynamics towards fission, suppression of fusion, an increase in apoptosis-related mitochondrial proteolysis and an onset of mitophagy. These changes indicate that H/R stress induces mitochondrial injury in M. edulis requiring upregulation of the protective mechanisms to segregate the dysfunctional mitochondria by fission and degrade the oxidative damaged proteins and/or organelles. Unlike mussels, the transcript levels of all studied genes in the oysters remained at the baseline (normoxic) levels during H/R stress. This muted transcriptional response of C. gigas is in agreement with earlier findings showing better ability to maintain cellular homeostasis and higher resistance to apoptosis during H/R stress in the oysters compared with the mussels. The revealed species-specific differences in the expression of the mitochondrial quality control pathways shed light on the potentially important mechanisms of mitochondrial protection against H/R-induced damage that might contribute to hypoxia tolerance in marine bivalves.